Komposisi Jenis-Jenis Pakan Anoa Di Kawasan Hutan Pendidikan Universitas Tadulako Kecamatan Bolano Lambunu Kabupaten Parigi Moutong - Tangkoro, Iver Thomas Pirimoi; Labiro, Elhayat; Korja, I Nengah (Jurnal Warta Rimba, 2018)
Sulawesi is one of island which large and imprortant in Indonesia. Geographically, the island including as Wallacea area. The area consists of Sulawesi island, Maluku, Banda Island, and small islands in Nusa Tenggara. The are of forest education has the width ± 6000 Ha which has diversity of flora and fauna. The species of flora that were found in this area are woody and not woody plants, meanwhile the fauna consisted of mammals, aves, reptiles, amphibians etc. There were some species of endemic fauna and rare as well as endangered, it need to preserve. One of them is Anoa (Bubalus sp). The study used was descriptive method. In deciding sample, it applied purposive sampling based on traces, puddles, resting place, and foraging of Anoa (Bubalus sp). Plant species that can be forage for Anoa (Bubalus sp) were 30 species of forages vegetation type that found 22 types become the forage of Anoa (Bubalus sp) either tree level, pole, sapling, and seedling or undergrowth . The highest of INP value on the tree level Lengaru ( Macaranga hispida (blume) Mull Arg ) is 44,660 %. At the pole stage, there is Ara ( Moraceae ) 44,281 %, the sapling level is Jongi (Podocarpus nerifolius d.don) 52,820 % and seedling or undergrowth is fern (pronephirum sp) 34,386 %Keywords: Anoa, Compositition, Educational Forest